2016
DOI: 10.1074/jbc.m115.702316
|View full text |Cite
|
Sign up to set email alerts
|

The Thumb Domain Mediates Acid-sensing Ion Channel Desensitization

Abstract: Acid-sensing ion channels (ASICs) are cation-selective proton-gated channels expressed in neurons that participate in diverse physiological processes, including nociception, synaptic plasticity, learning, and memory. ASIC subunits contain intracellular N and C termini, two transmembrane domains that constitute the pore, and a large extracellular loop with defined domains termed the finger, ␤-ball, thumb, palm, and knuckle. Here we examined the contribution of the finger, ␤-ball, and thumb domains to activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 56 publications
5
29
0
Order By: Relevance
“…Some mutants displayed up to twofold accelerated kinetics of current decay (Fig. S1A), in accordance with previous studies that described altered current kinetics of AcP mutants (15,16). Some mutants showed a sustained current, which was, however, small in all mutants except AcP16b (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Some mutants displayed up to twofold accelerated kinetics of current decay (Fig. S1A), in accordance with previous studies that described altered current kinetics of AcP mutants (15,16). Some mutants showed a sustained current, which was, however, small in all mutants except AcP16b (Fig.…”
Section: Resultssupporting
confidence: 91%
“…These observations are consistent with an important regulatory, but not essential, role of the AcP in ASIC activation. The AcP also controls the kinetics and pH dependence of desensitization (15,16,27), a role that is underlined here by the slow ΔF signals, which may reflect conformational changes leading to desensitization. In ENaC, the AcP may also have a regulatory role, because it was shown to contain a binding site for Na + involved in channel inhibition (31).…”
Section: Discussionmentioning
confidence: 84%
“…Voltage clamp fluorometry (VCF) analysis provided evidence of conformational changes in the acidic pocket correlated to activation and desensitization, and proposed a likely sequence of conformational changes in the acidic pocket upon extracellular acidification 42 . Furthermore, studies with ASIC1a–ASIC2a chimeras showed that swapping the thumb domain between subunits results in faster channel desensitization 43 . Likewise, the covalent modification of Cys residues at selected positions in the β-ball–thumb interface accelerated the desensitization of the mutant channels 43 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, intersubunit cross-linking between thumb and palm domains alters ENaC activity in a length-dependent manner (52). Furthermore, there is evidence that ASIC1 thumb domain interactions with the ␤-ball and palm domains influence channel gating (53,54). The recently published closed state structure of ASIC1 highlights a prominent role of the thumb domains in channel gating (55).…”
Section: Enac Thumb Domainmentioning
confidence: 99%